The effect of combination treatment of vascular endothelial growth factor receptor 3 inhibitor, MAZ-51, and zingerone on melanoma cell proliferation - Hlophe, Yvette Nkondo (University of Pretoria, 2025)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2024.